Pharmacokinetic Study of Non–steroidal Anti–inflammatory Drugs in Wildlife Rehabilitation Birds - Caruso, Sara; Miller, Erica; Poppenga, Robert (Wildlife Rehabilitation Bulletin, 2006)
While the use of non–steroidal anti–inflammatory drugs (NSAIDs) is common in many veterinary practices, there is little information on the efficacy and appropriate dosage levels in avian species. This study examined the pharmacokinetics of one NSAID, meloxicam, given orally to wild birds undergoing rehabilitation. Meloxicam was administered at 1 mg/kg. The primary species studied was Canada goose, but red–tailed hawk was included as a comparison between these species of birds. After administration of meloxicam, blood samples were taken at a series of time intervals to determine the concentration of drug in the serum over time. The study concluded that 1 mg/kg is an appropriate dosage but should be administered twice daily instead of once a day due to the elimination rate in Canada geese. These results suggest that red–tailed hawks absorb and eliminate meloxicam at a different rate, but additional studies are needed to confirm this finding.